Enhancing Interest in Learning Qur'an and Hadith: Development of an E-Module for MTs Bustanul Ulum Students in Central Lampung - Ahmad Zakky Asnawi; Jamal Fakhri; Waluyo Erry Wahyudi; Shendra R. S. Abuissac (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
This study aims to develop an e-module that can enhance students' interest in learning the Qur'an and Hadith material at MTs Bustanul Ulum, Central Lampung. Using the Research and Development (R&D) method with the ADDIE model, this research follows five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation results from three experts (content, language, and design) show that this e-module is highly feasible, with scores of 92.5% for content and language validity, and 86% for design validity. Both small and large-scale trials showed positive results, with significant improvements in students' learning interest, reflected in the increase in pre-test and post-test scores. In class VII-a, student interest increased from 54% to 73%, and in class VII-b, it increased from 61% to 70%. Correlation analysis results showed a positive relationship between e-module use and academic performance improvement, with a correlation coefficient of 0.62 (p < 0.05). This study also integrates the Sustainable Development Goals (SDGs) into the e-module material, providing a learning experience relevant to global challenges. However, this study has limitations, including a small sample size limited to a single school, so the results cannot yet be generalized to broader contexts. Further research with a larger and more diverse sample, as well as measuring the long-term impact on knowledge retention and academic achievement, is necessary to deepen the understanding of the effectiveness of e-modules in Qur'an and Hadith education.